KUALITAS PELAYANAN KANTOR OMBUDSMAN REPUBLIK INDONESIA PERWAKILAN SULAWESI UTARA - Rorong, Lucky L. N; Rares, Joyce J; Waworundeng, Welly; Londa, Very Y (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2025)
This study aims to evaluate the quality of public service delivery at the North Sulawesi Regional Office of the Indonesian Ombudsman in the context of implementing Law No. 25 of 2009 on Public Services and Law No. 37 of 2008 on the Ombudsman of the Republic of Indonesia. The findings reveal that, in general, the quality of public services provided has not yet reached an optimal level. Key issues include the mismatch between staff competencies and organizational needs, unclear service procedures, delays in complaint handling, and suboptimal use of information technology. Further challenges involve the lack of alignment in vision between leadership and staff, limited employee involvement in planning, and the underutilization of public satisfaction surveys for service evaluation. Based on an analysis of seven service quality dimensions—self-esteem, exceed expectation, recovery, vision, improve, care, and empower—each aspect faces both structural and cultural obstacles. Therefore, strong leadership, digital service innovation, enhanced human resource capacity, and strengthened internal supervision and empowerment are essential to achieving responsive and high-quality public service delivery.